Saliva as a diagnostic tool in forensic odontology - Jessica Jessica; Elza I. Auerkari (Journal of Dentomaxillofacial Science, 2019)
Objective: This paper aims to review the studies of the saliva analysis for forensic odontology purposes, starting from identifying the saliva stain and extracting the saliva sample.Methods: A literature review was performed using textbook (2016) and online search in scientific databases: PubMed®, ScienceDirect®, JDMFS online, EBSCOhost® (from 2002 to 2017). The studies generated were screened and selected by a single examiner based on the following criteria: full text articles with abstracts reporting on saliva and forensic odontology or personal identification and all articles are written in English.Results: From the articles gained by the author, the author found that saliva stain can be detected through many ways and can be extracted using single swab or double swab technique. Saliva analysis can be used to detect drug and hormone abuse, to detect intoxication, to identify suspects and victims of a crime or disaster, and also to identify bitemark’s perpetrator. Conclusion: Saliva is a very useful diagnostic tool in forensic odontology. Its detection and analysis is very important in verifying the existence of a crime, in identifying suspects and victims of a crime, and in personal identification in mass disaster.  Despite all the usefulness of saliva analysis, the existence of saliva in crime scene is often difficult to be confirmed, therefore it is better to combine more than one saliva stain identification tool to confirm.